SEVENTH DAY ADVENTIST CHURCH’S VIEW ABOUT HOLY COMMUNION ACCORDING TO JOHN 13:4-17 - sinaga, Polman; Hutagalung, Stimson; Ferinia, Rolyana (International Journal of Social Science, 2022)
The Lord's Supper is a sacred ecclesiastical ceremony and this is the example set by Jesus. The Holy Communion is a symbol of the sacrifice Jesus made on the cross for the purpose of human salvation. The Holy Communion ceremony is not just an ecclesiastical event but has spiritual meanings such as: a memorial of God's mercy, a higher form of cleansing, a fellowship of forgiveness, is God's command, and contains God's blessing. This study uses a qualitative literature study method that describes descriptively the meaning of the Holy Communion according to the view of the Seventh-day Adventist Church, and the results of this study are so that everyone can better understand the meaning of the Holy Communion ceremony so that they can further build spiritual faith and understand the meaning of Jesus' sacrifice which is symbolized through the ceremony. Holy communion.